2000
DOI: 10.1590/s0100-204x2000001200006
|View full text |Cite
|
Sign up to set email alerts
|

Emergência do capim-marmelada em duas regiões do estado do Paraná

Abstract: EMERGENCE OF BRACHIARIA PLANTAGINEA (LINK) HITCH. IN TWO REGIONS OF PARANÁ STATE, BRAZILABSTRACT -The objective of this experiment was to determine the periodicity and intensity of emergence as well as the survival of Brachiaria plantaginea (Link) Hitch. seeds in two regions of Paraná State, Brazil. A randomized complete block in factorial design 2 x 3 x 2, with three replications was used. The factors studied were: seed survival in the soil; seed burial depth, and soil management. Ceramic cylinders were insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
1
0
3
Order By: Relevance
“…(11,17,24,31,38, and 45 days after soybean emergence -DAE -for seeding performed 1 DAD,and 8,15,22,29,36,and presença, em comunidades mistas de ervas, for superior a 70% em ocupação do espaço . A agressividade e o sucesso competitivo do papuã se devem, entre outros fatores, à produção de abundantes dissemínulos, à germinação distribuída ao longo do ciclo da cultura e à morfologia de planta que leva à formação de dossel vigoroso, com folhas sobressaindo acima do dossel da soja (Martins, 1994;Rodrigues et al, 2000). Na mesma linha, Kissmann (1991) salienta que o desenvolvimento de papuã pode ser tão vigoroso que uma planta m -2 chega a afetar em 50% o rendimento da soja.…”
unclassified
“…(11,17,24,31,38, and 45 days after soybean emergence -DAE -for seeding performed 1 DAD,and 8,15,22,29,36,and presença, em comunidades mistas de ervas, for superior a 70% em ocupação do espaço . A agressividade e o sucesso competitivo do papuã se devem, entre outros fatores, à produção de abundantes dissemínulos, à germinação distribuída ao longo do ciclo da cultura e à morfologia de planta que leva à formação de dossel vigoroso, com folhas sobressaindo acima do dossel da soja (Martins, 1994;Rodrigues et al, 2000). Na mesma linha, Kissmann (1991) salienta que o desenvolvimento de papuã pode ser tão vigoroso que uma planta m -2 chega a afetar em 50% o rendimento da soja.…”
unclassified
“…Although Brachiaria plantaginea (Link) Hitch (Alexandergrass) is not the most important weed in Triticum aestivum L. (wheat crop), this species is frequently found in areas cropped with this cereal in the South of Brazil. Rodrigues et al (2000) reported that, although the Alexandergrass emergence is more frequent in summer season, it can also emerge substantially in winter season and then infest winter crops. Moreover, this species is resistant to ACCase inhibitor herbicides commonly used in soybean in a rotation with wheat (Christoffoleti et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Os sistemas de cultivo são os principais responsáveis pela distribuição vertical de sementes (Gonzalez-Andujar, 1997; Lacerda, 2003), que varia de acordo com o tipo, a velocidade e a profundidade de trabalho do implemento agrícola utilizado, além da textura e umidade do solo (Carmona, 1992). Por exemplo, em solos não movimentados a concentração de sementes é maior nas primeiras camadas; já em solos movimentados a distribuição das sementes é uniforme entre as diferentes camadas (Rodrigues et al, 2000). Em geral, sementes colocadas em maiores profundidades abaixo da superfície do solo conservam melhor a sua capacidade de germinar (Freitas, 1990).…”
unclassified
“…Em geral, sementes colocadas em maiores profundidades abaixo da superfície do solo conservam melhor a sua capacidade de germinar (Freitas, 1990). Assim, as maiores taxas de emergência oc or re m em pr of un di da de s me no re s de enterramento (Rodrigues et al, 2000).…”
unclassified